2012
DOI: 10.1029/2011jc007345
|View full text |Cite
|
Sign up to set email alerts
|

Variability of phytoplankton light absorption in Canadian Arctic seas

Abstract: Phytoplankton light absorption spectra (aϕ(λ)) were measured in the Canadian Arctic (i.e., the Amundsen Gulf, Canadian Arctic Archipelago, northern Baffin Bay and the Hudson Bay system) to improve algorithms used in remote‐sensing models of primary production. The absorption by algae, dominated by picophytoplankton (<5 μm), was not the major light absorption factor in the four provinces; the colored dissolved organic matter (CDOM) contributed up to 70% of total light absorption. During the fall, the low total … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
29
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 101 publications
(125 reference statements)
5
29
0
Order By: Relevance
“…± < 0.001 µg C (µg chl a) −1 h −1 (µmol quanta m −2 s −1 ) −1 ) over the depth interval that separates surface and SCM samples in our study. Such a shift is similar to the statistical error attached to α estimates obtained with the 13 C method (here ± 11 % for a mean value of 0.027) and one order of magnitude smaller than the observed range of α values (0.027 ± 0.014; see also Brunelle et al, 2012) SCM communities located in a strongly stratified environment would benefit by acclimating to low irradiance. For C uptake, this expectation is consistent with the contrast between the data of Platt et al (1982), who found no vertical differences in uptake-irradiance parameters in weakly stratified waters (Baffin Bay), and our data set, where α was higher at the SCM than at the surface.…”
Section: Acclimation and Vertical Coupling Of C And N Uptakesupporting
confidence: 80%
“…± < 0.001 µg C (µg chl a) −1 h −1 (µmol quanta m −2 s −1 ) −1 ) over the depth interval that separates surface and SCM samples in our study. Such a shift is similar to the statistical error attached to α estimates obtained with the 13 C method (here ± 11 % for a mean value of 0.027) and one order of magnitude smaller than the observed range of α values (0.027 ± 0.014; see also Brunelle et al, 2012) SCM communities located in a strongly stratified environment would benefit by acclimating to low irradiance. For C uptake, this expectation is consistent with the contrast between the data of Platt et al (1982), who found no vertical differences in uptake-irradiance parameters in weakly stratified waters (Baffin Bay), and our data set, where α was higher at the SCM than at the surface.…”
Section: Acclimation and Vertical Coupling Of C And N Uptakesupporting
confidence: 80%
“…In the western Arctic, we do not expect a dg (λ) to covary with C a as it does in lower latitude and oligotrophic oceans . High levels of CDOM in Arctic Ocean waters have been widely documented (e.g., Brunelle et al, 2012;Granskog et al, 2012;Guéguen et al, 2005;Matsuoka et al, 2013aMatsuoka et al, , 2011Matsuoka et al, , 2007Pegau, 2002;Stedmon et al, 2011). The basin as a whole receives the largest dissolved organic carbon input (and hence CDOM input) from rivers, relative to its size, than any other ocean basin (Rachold et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…In the Labrador Sea, the OC4 algorithm was found to underestimate C a by 50% over most of its dynamic range , while in the western Arctic Ocean (i.e., Beaufort and Chukchi seas) and the Arctic region of the Atlantic, the bias has been consistently towards overestimation (Ben Mustapha et al, 2012;Matsuoka et al, 2007;Stramska et al, 2003;Wang and Cota, 2003). Atypically high absorption by chromophoric dissolved organic matter (CDOM) from river inputs to this Arctic region has been suggested as the main cause for C a overestimation from satellite radiometry (Brunelle et al, 2012;Matsuoka et al, 2007). Attempts at developing regionally tuned C a for the Arctic (Cota et al, 2004;Wang and Cota, 2003) have had mixed successes (Ben Mustapha et al, 2012;Matsuoka et al, 2007).…”
Section: Introductionmentioning
confidence: 94%
“…Historical observations were complemented only much more recently by measurements made in ice-free waters (Wang and Cota, 2003;Matsuoka et al, 2007Matsuoka et al, , 2009Matsuoka et al, , 2011Hill, 2008;Ben Mustapha et al, 2012;Brunelle et al, 2012), and no other measurements have been reported in between in the open literature, at least to our knowledge. Therefore, attenuation and reflectance properties of Arctic waters are still poorly known.…”
Section: Antoine Et Al: Apparent Optical Properties Of the Canadimentioning
confidence: 99%